STUDI HUBUNGAN PEMERINTAH DESA DENGAN BADAN PERMUSYAWARATAN DESA DALAM PEMBUATAN PERATURAN DESA DI DESA KONANG, KECAMATAN GLAGAH, KABUPATEN LAMONGAN - Adi Rivanto, M. Zulham (Universitas 17 Agustus 1945 Surabaya, 2015)
Study of village goverment relationship with village conference department in avillage regulation construction in Konang Village, Subdistrict Glagah, LamonganRegency. The relationship between village goverment with village conferencedepartment in a Konang village regulation construction based on each duty, rightauthority, and obligation legally as work partners. This study is conducted toknow the mechanism of village regulation construction in Konang village, therelation between village conference department with Konang village goverment inan arrangement of village regulation and a result of village regulation at 2015 thathave been arranged and assigned by the village conference department in thepartnership with village goverment. Based on the result of the study, themechanism of regulation arrangement in Konang village is devided intopreparation step that includes of planning and preparation, and process thatincludes of formulation step, discussion, and arrangement technique, and assignedstep, invitation, and dissemination. The village conference department with theKonang Headman have good relationship. It happen because the villageconference department and Konang village govertment have carried out their eachduty and right authority in the village regulation arrangement.The villageregulation that have been constructed and assigned by the village conferencedepartment with Konang village goverment have been run well.Key words : relationship, village goverment, village conference department, andvillage regulation.